Micro RNAs in Tfh regulation: Small molecules with a big impact. Issue 2 (2nd February 2021) - Basto, Afonso P.; Graca, Luis
Abstract: The germinal center (GC) reactions are critical for the production of high‐affinity antibodies that comprise the protective humoral response elicited by infection or vaccination. GCs are initiated through the interaction of B cells with T follicular helper (Tfh) cells. While the transcriptional regulation of Tfh differentiation has been studied in great detail, the impact of micro RNAs (miRNAs) on Tfh development and stability has been harder to address. It was previously shown that a complete deletion of miRNAs biogenesis prevents Tfh differentiation. In this issue of the European Journal of Immunology [Eur. J. Immunol. 2021. 51: 408‐413], Zeiträg et al. use an inducible gene deletion approach to reveal that miRNAs are also required for the maintenance of Tfh cells induced following viral infection in mice. These results provide new clues to the regulation of GC responses through Tfh and T follicular regulatory cells. Abstract : Production of miRNAs is essential for the development of Tfh cells. Elimination of miRNA production before viral (LCMV) infection abrogates Tfh formation. It was now shown that the maintenance of Tfh cells also requires miRNAs because miRNA ablation after viral infection leads to a reduction of Tfh cell number.